2008
DOI: 10.1111/j.1439-0426.2001.00243.x
|View full text |Cite
|
Sign up to set email alerts
|

Viability, growth and external morphology of meiotic- and mitotic-gynogenetic diploids in red sea bream, Pagrus major

Abstract: Two types of gynogenetic diploids were arti®cially induced in the red sea bream (Pagrus major Temminck et Schlegel), either by suppressing the ®rst cell cleavage (mitotic-G2N) or by retaining the second polar body (meiotic-G2N). The eggs of red sea bream were inseminated with UV-irradiated (3000 erg mm )2 ) sperm of Japanese parrot ®sh (Oplegnathus fasciatus Temminck et Schlegel), and hydrostatic pressure shock of 700 kg cm )2 for 5.5 min at 46 min after insemination (mitotic-G2N) and cold shock of 1°C for 30 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Through a combining approach of artificial gynogenesis and sex reversal, all-female population was also produced in common carp and used for aquaculture practice [60]. Recently, artificial gynogenesis has been performed in many marine fish species, such as flounder [168], red sea bream (Pagrosomus major) [169], sea bass [170], spotted halibut (Verasper variegatus) [171], and half-smooth tongue soles [172]. Generally, the gynogenetic offspring is composed of all-females.…”
Section: Artificial Gynogenesis and All-female Population Productionmentioning
confidence: 99%
“…Through a combining approach of artificial gynogenesis and sex reversal, all-female population was also produced in common carp and used for aquaculture practice [60]. Recently, artificial gynogenesis has been performed in many marine fish species, such as flounder [168], red sea bream (Pagrosomus major) [169], sea bass [170], spotted halibut (Verasper variegatus) [171], and half-smooth tongue soles [172]. Generally, the gynogenetic offspring is composed of all-females.…”
Section: Artificial Gynogenesis and All-female Population Productionmentioning
confidence: 99%
“…In fact, many studies have shown that morphometric variations occur during inbreeding. Kato et al (2001) studied the external morphological variation in red seabeam (Pagrus major) between two types of gynogenetic diploids and normal diploids. Leary et al (1983) argued that inbreeding may affect the developmental stability of morphometric traits, because the lack of enzymatic diversity in homozygotes reduces the efficiency of normal developmental homeostatic processes.…”
Section: Genetic Effects On Morphological Variation During Inbreedingmentioning
confidence: 99%